Screening for latent tuberculosis infection: performance of tuberculin skin test and interferon-γ release assays under real-life conditions. Issue 11 (14th May 2012) - Kleinert, S; Tony, H-P; Krueger, K; Detert, J; Mielke, F; Rockwitz, K; Schwenke, R; Burmester, G R; Diel, R; Feuchtenberger, M; Kneitz, C
Abstract : Objectives: To characterise optimal screening strategies for latent tuberculosis infection (LTBI) prior to the initiation of anti-tumour necrosis factor therapy. Methods: Patients in 62 German rheumatology centres were evaluated for LTBI. Each patient was screened with a tuberculin skin test (TST) and one form of an interferon-γ release assay (IGRA), either TSPOT.TB (TSPOT) or Quantiferon TB Gold (QFT). Results: A total of 1529 patients with rheumatological disease were tested with a TST, 844 with TSPOT and 685 with QFT. TST was positive in 11.3% (n=173). The prevalence of LTBI was 8.0% when defined as a positive TST and no previous Bacille Calmette-Guérin (BCG) vaccination and 7.9% when based on a positive IGRA. Combining both estimates increased the prevalence of LTBI to 11.1%. Clinical risk factors for LTBI were found in 122 patients (34 with a history of prior TB, 81 close contacts and 27 with suggestive chest x-ray lesions). A compound risk factor (CRF) was defined as the presence of at least one of these three risk factors. Statistical analyses were conducted to examine the association between CRF and LTBI test outcomes. In multivariate analysis, TST was influenced by CRF (OR 6.2; CI 4.08 to 9.44, p<0.001) and BCG vaccination status (OR 2.9; CI 2.00 to 4.35, p<0.001). QFT and TSPOT were only influenced by CRF (QFT: OR 2.6; CI 1.15 to 5.98, p=0.021; TSPOT: OR 8.7; CI 4.83 to 15.82, p<0.001). ORs and the agreement of TST and IGRA test results varied by rheumatological disease. Conclusion: LTBI test results in an individual patient need to be considered in the context of prior BCG vaccination and clinical risk factors. In patient populations with low rates of TB incidence and BCG vaccination, the use of both TST and IGRA may maximise sensitivity in detecting LTBI but may also reduce specificity.